2010
DOI: 10.1243/09544062jmes1993
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and suppression of inconsistent natural frequency and mode coupling of a cylindrical ultrasonic stator

Abstract: Inconsistent frequency and mode coupling are primary concerns of ultrasonic motors. These modal properties are influenced by motor features, including piezoelectric ceramics, stator teeth, or other supports attached on a stator. While this influence is understood intuitively and has been studied numerically, they have not been clarified analytically. This work develops the analytical model of the example cylindrical stator and uses it to study the influence of the features on the modal properties. In this mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Although the rectangular prism stator and a through-shaft mobile element provide a compact design, mode coupling as the drive method of the motor limits its use when the motor is subjected to unpredicted conditions. These unpredicted conditions affect the resonance frequency of the coupled modes [35]. Since mode coupling is obtained at a specific frequency where the resonance frequencies of two modes match, shifting resonance frequencies of the modes in different directions abolish the driving conditions.…”
Section: • Cylindrical (Translational-rotary) Piezoelectric Motorsmentioning
confidence: 99%
“…Although the rectangular prism stator and a through-shaft mobile element provide a compact design, mode coupling as the drive method of the motor limits its use when the motor is subjected to unpredicted conditions. These unpredicted conditions affect the resonance frequency of the coupled modes [35]. Since mode coupling is obtained at a specific frequency where the resonance frequencies of two modes match, shifting resonance frequencies of the modes in different directions abolish the driving conditions.…”
Section: • Cylindrical (Translational-rotary) Piezoelectric Motorsmentioning
confidence: 99%
“…37 A further search throughout the existing studies implies: (1) most researchers employed the perturbation method but the deviation from the axisymmetry can be remarkable. (2) Some examined the splitting in the context of unshifted standard structures, 5,6,9,[12][13][14][21][22][23] with the exception of Fox et al 3,10,15 and Parker et al 18,27,39 Since symmetry is normally a primary concern in practice, research on general symmetric topologies is necessary. (3) Most researchers focused on the splitting for one wavenumber only, but Fox et al 3 aimed at two at the expense of the symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency splitting and mode contamination are key issues discussed in the existing literature available on this subject [18][19][20][21][22][23][24][25][26]. Wickert and colleagues [18][19][20][21] studied disk-shaped periodic structures using the perturbation method, and found that if the feature number N is even, the contaminated wave orders on the n base wave number can be defined as those m satisfying the criterion jn6mj ¼ N, 2N, 3N,… for repeated modes, and m ¼ N, 2N, 3N,… for splitting modes.…”
Section: Introductionmentioning
confidence: 99%
“…Wu and Parker [22] studied ringshaped structures by using the perturbation and Galerkin analysis and obtained the corresponding splitting and contamination criteria. Using the perturbation idea [18][19][20][21], authors of this work dealt with the modal behaviors of cylindrical ultrasonic stators [25]. Kumar and Krousgrill [26] also examined these on the basis of disk-shaped ultrasonic stators.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation